Advertisement call of Dendropsophus studerae (Carvalho-e-Silva, Carvalho-e-Silva and Izecksohn, 2003) (Anura: Hylidae), with new record and geographic distribution extension - Napoli, Marcelo Felgueiras; de Abreu, Rafael Oliveira; Cruz, Deise; Herrera, Jocilene Brandão; Petersen, Emanuela; Klein, Wilfried (Zootaxa, 2014)
The treefrog genus Dendropsophus Fitzinger comprises 95 species, with geographic distribution from northern Argentina and Uruguay north through tropical South and Central America to tropical southern Mexico (Frost 2014). Dendropsophus studerae was included in the D. microcephalus clade by Faivovich et al. (2005), which currently consists of 39 species (Frost 2014). The species that most resembles D. studerae is D. bipunctatus (Spix), as already stated in the original description of the former (Carvalho-e-Silva et al. 2003). Thus far, Dendropsophus studerae was only known from its type locality, in the municipality of Quebrangulo (09º19’08”S, 36º28’16”W), State of Alagoas, northeastern Brazil. The original description of the species also included data on its eggs, tadpole (oral disc and external morphology) and some natural history information of adults and larvae, but its advertisement call remains undescribed.